Rosana Paulino: about invented natures on black bodies (Palíndromo, 2024)
The objective of this article is to present an analysis of works by artist Rosana Paulino, developed using archive images from the historical period of colonial Brazil, when invented natures of black bodies were created, with the purpose of justifying hierarchical relationships between races, through pseudoscientific proof. To do this, we take a closer look at the  procedures, critical constructions and callings present in the artist’s book ¿História natural? By extension, we also work with theoretical considerations conveyed in the literature on art and descolonial criticism. We verify the strength of a production that subverts mechanisms of downgrading and exclusion from the past, which still echoes today, with a creation that constitutes a call,  through art, to other ways of life that consider respect for differences and  equal rights.
Keywords: Rosana Paulino; Visual Arts; Descolonial criticism; Racial discrimination